Next Generation of Evidence Collecting: The Need for Digital Forensics in Criminal Justice Education - Scott H. Belshaw (Journal of Cybersecurity Education, Research & Practice, 2019)
Digital forensics poses significant challenges to law enforcement as the information found in a computer system is often present at most crime scenes in the form of computer data and cell phones. Digital evidence contained on common devices, such as cell phones and laptops, includes information that can be pertinent to the investigation of crimes. Law enforcement is increasingly identifying the need to be able to process their evidence internally warranting the exploration of the need for digital forensics training as part of a broader study of criminal justice for future law enforcement practitioners. This paper uses telephone surveys of police agencies in the North Texas area to explore their capabilities and need for trained digital forensic examiners (n=42). Findings suggest that digital forensic education is needed as most police examiners are trained first as police officers and secondly as digital forensics examiners. Future education challenges and policy implications are discussed.